Enhancing Early Childhood Learning Quality through Adaptive Management - Chodijah, Siti; Laili, Nikmatul; Fauziyah, Asmaul; Ravellina, Putri Novitrianti; Safitri, Dewi; Rerka, Agustina Ensanyana; Azminah, Suhartini Nurul (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
The purpose of this study is to analyse the early childhood education management strategies aimed at improving the quality of student learning. The basic problem stems from the challenges in managing early childhood education, particularly in terms of limited human resources, curriculum adaptation, and the need for strengthening learning quality that focuses on children's character and interests. This study employs a qualitative descriptive approach, utilizing data collection techniques such as observation, documentation, and interviews with the principal, educators, and educational staff. The data analysis is conducted through triangulation, reduction, presentation, and conclusion drawing, along with data validation tests. The findings reveal that the educational management strategy is carried out through planning, organizing, implementation, and supervision functions. The learning planning is detailed based on the Merdeka curriculum, taking into account the students' needs and characteristics. Organizing is done flexibly by distributing educator tasks in accordance with the needs and adapting to the limitations of human resources. The learning implementation focuses on character development, interest and talent enhancement, and child-centre play principles as the main focus of educational activities. Supervision is carried out by the principal with communicative supervision to conduct internal and cooperative monitoring. This management strategy has a positive impact on the improvement of learning quality, educator professionalism, and active student involvement. The study recommends strengthening human resource management through continuous training and further research on developing an adaptive and inclusive early childhood education management model.